Todd LeVasseur, Pramod Parajuli, and Norman Wirzba (eds.), Religion and Sustainable Agriculture: World Spiritual Traditions and Food Ethics. (28th May 2018) - Nabhan, Gary
Abstract : Todd LeVasseur, Pramod Parajuli, and Norman Wirzba (eds.), Religion and Sustainable Agriculture: World Spiritual Traditions and Food Ethics (Lexington: University Press of Kentucky, 2016), 394pp., $50.00 (hardcover), ISBN: 978-0-8131-6797-8.